Arguedian answer to a Vargasllosan question. Rafael Dumett’s El espía del Inca - García-Bedoya Maguiña, Carlos (2021)
Rafael Dumett's novel El espía del Inca (Lluvia Editores, 2018) is, among many things, the best Peruvian novel of the 21st century, but it is also an answer to Vargas Llosa's famous question: when did Peru get fucked up? Dumett looks for the answer to this question in the only place where it can be found: in history.